Troska biskupa Czesława Domina o wiernych świeckich w świetle dekretów powizytacyjnych parafii diecezji koszalińsko-kołobrzeskiej - Dullak, Kazimierz (Prawo Kanoniczne, 2007)
The Canon Law Code which is obliging within the Catholic Church, obliges the diocesan bishop to pay pastoral visits within his diocese (can. 396 § 1). The Vatican Council II points out that the bishops should run the particular churches entrusted to them, by counsels, encouragem ents and example, and that they should do it by the power of their authority (LG 27). During his 4-year pastoral work in the diocese of Koszalin and Kolobrzeg, bishop Czeslaw Domin visited 55 parishes. In each one of them he was concerned not only about the priests, but also lay people, and especially their spiritual lives. Bishop Domin was undertaking some actions aimed to revive charity activities within the parishes. Also, he was encouraging pastoral care for married couples and families, and tried to change things concerning religious education in public schools. He was always encouraging parishioners to be more active in different church activities.